Employment Law Counseling for Lecturers and Staff at Wira Bhakti Singaraja High School - Adiwidya, I Made; Juniasa, I Dewa Nyoman; Yuda Ariawan, Dewa Agus (Abdi Masyarakat, 2025)
This Community Service aims to improve legal knowledge for teachers and employees at SMA Wira Bhakti Singaraja, especially regarding employment. Community Service is carried out at SMA Wira Bhakti Singaraja. The location of the service was chosen deliberately, on the grounds that SMA Wira Bhakti Singaraja is one of the private schools where teachers and employees receive legal protection based on Law Number 13 of 2003 concerning Employment (Labor Law). The target audience for this Community Service activity is teachers and employees at SMA Wira Bhakti Singaraja, totaling 15 people. 12 teachers and 3 employees. In this Community Service, data is analyzed using qualitative analysis, namely the data and facts found will be described. The results obtained from the community service activities of labor law counseling for teachers and employees at SMA Wira Bhakti Singaraja are the increase in insight and knowledge of counseling participants regarding aspects of labor law and mechanisms for resolving industrial relations disputes. With this counseling, teachers and employees can understand their rights and obligations protected by the Manpower Act. So with this understanding, industrial relations can be implemented properly.